Traces Behind the Esmeraldas Shore - DeBoer, Warren R. (Book collections on Project MUSE., 1996)
"Survey along the lower Cayapas and Santiago rivers located ca. 200 habitation sites. Ceramic distinctions define seven phases, partly sequential and partly regional; 25 C14 dates extend from ca. 400 BC to AD 1400. Settlements become smaller, more dispersed, and culturally isolated after ca. AD 400"--Handbook of Latin American Studies, v. 57.